The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17925/use.2017.13.01.01
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Rare Association Between Right Thyroid Hemiagenesis, Lingual Thyroid, and Papillary Thyroid Cancer

Abstract: Lingual thyroid and thyroid hemiagenesis are rare thyroid developmental abnormalities. These conditions can be present with other thyroid diseases, whether functional ones involving abnormal thyroid hormone levels, or structural ones such as presence of thyroid nodules, however the association with thyroid cancer and lingual thyroid or thyroid hemiagenesis is rare. In addition to that, when thyroid hemiagenesis is present, it is usually in the left lobe. We describe here a pregnant patient who presented with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In the ninth month of evaluation, thyroid USG evaluation revealed fibrotic tissue in the right thyroid bed and bilateral lymphadenopathy, although there was no recurrence complains. This is in line with a study by Azmat et al, which stated a key finding of thyroid cancer accompanying TH suspicion is a metastatic cervical node.6 However, the association between TH and thyroid cancer is uncommon [6] . Moreover, the possibility of an ectopic thyroid tissue is also need to consider.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the ninth month of evaluation, thyroid USG evaluation revealed fibrotic tissue in the right thyroid bed and bilateral lymphadenopathy, although there was no recurrence complains. This is in line with a study by Azmat et al, which stated a key finding of thyroid cancer accompanying TH suspicion is a metastatic cervical node.6 However, the association between TH and thyroid cancer is uncommon [6] . Moreover, the possibility of an ectopic thyroid tissue is also need to consider.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a literature review, thyroid malignancies were reported in only 3% of TH cases [5] . Similarly, ectopic thyroid tissues were also reported in 3% of cases [6] . It is more common in female patients and the majority includes left lobe hemiagenesis comprising more than 80% of all diagnosed cases [2] , [5] , [7] .…”
Section: Introductionmentioning
confidence: 85%